The Impact of Teaching Style and Course Structure on Intermediate Accounting Students Understanding - Sudarto, Triadi Agung; Juliardi, Dodik (International Journal of Business, Law, and Education, 2024)
Many students face great difficulties in completing Intermediate Accounting courses well. One of the factors that is considered influential is the teaching style. Another factor that can affect students' understanding in studying Intermediate Accounting is the learning structure (course structure). A good learning must include the correct and coherent choice of topics in order to present the learner's point of view and not only from the point of view of experts, in this case lecturers (experts). Based on the results of the research test, the following results can be obtained: 1) Teaching Style has a significant positive effect on students' understanding of the Intermediate Accounting Course; 2) Course Structure has a significant positive effect on Student Understanding in the Intermediate Financial Accounting Course. The implication of this study is that the application of the theory of interpersonal behavior is answered. The results show that this theory can be a valuable tool for understanding and improving interpersonal relationships, and for identifying strategies for solving problems. Furthermore, the practical implications show that the existence of the right teaching style and a course structure that is structured and based on the principle of interrelation between materials can increase student learning motivation because students feel that they can follow the learning flow better. With a clear structure, students tend to understand the concept thoroughly and uninterruptedly